Comparative chemical composition and pesticidal evaluation of Acorus calamus accessions collected from different geographical locations - Joshi, Tisha; Nagarkoti, Kirti; Joshi, Navadha; Rawat, Avneesh; Prakash, Om; Kumar, Ravendra; Srivastava, Ravi Mohan; Kumar, Satya; Rawat, Shilpi; Rawat, Dharmendra Singh (European Journal of Chemistry, 2023)
The objectives of the present study were to investigate the phytochemical composition of essential oils (EO) from rhizomes of Acorus calamus collected from Jorhat, Assam; Munsyari and Pantnagar, Uttarakhand, India. EOs were studied for different pesticidal activities viz; nematicidal, insecticidal, and herbicidal activity. To study the synergistic effect of EOs on pesticidal activity, four combinations of EOs were prepared. Phenylpropanoids with β-asarone as the main compound were identified in all collections with varying percentages. Its contribution was found to be 85.8% in Munsyari EOs followed by 74.3% in Pantnagar and 62.6% in Assam collections. All EOs exhibited dose-dependent in vitro nematicidal activity against Meloidogyne incognita in terms of immobility and inhibition of egg hatching. The activity was observed as maximum in the EO combination of all three collections (1:1:1) whereas minimum in the Assam collections. In insecticidal activity against Lipaphis erysimi and Selepa celtis, maximum mortality was observed in Munsyari collections. The oils were assessed for sprout inhibition activity in terms of seed germination inhibition, coleoptile growth of the shoot and root against Raphanus raphanistrum. Maximum seed germination inhibition, % shoot, and root growth inhibition were found in all collections EO combinations. To predict the possible mode of action and the structure-activity relationship between major compounds of EOs and biological activities, in silico molecular docking and ADME/Tox studies were performed. The docking results revealed the mode of action of proteins of insects, nematodes, and weeds and were found in support of in vitro experiments. The study may be helpful for the development of herbal-based pesticides after proper clinical trials.